Survival, dispersal, and capture probability of male and female birds - Lovász,Lilla; Roth,Tobias; Karcza,Zsolt; Lukács,Katalin Odett; Gyurácz,József; Amrhein,Valentin (PeerJ Preprints, 2018)
In birds, observed adult sex ratios often are biased towards males. This bias could arise due to differences between sexes in dispersal or in detectability / catchability, but a preferred explanation has been sex differences in survival. However, most studies investigated apparent survival, in which differences in dispersal were not accounted for. Here, we used data from 24'830 capturesof 11 bird species, collected at 40 Hungarian constant effort ringing sites, to estimate true survival, dispersal, and capture probability. On average, dispersal and capture probabilities were similar between sexes. However, the probability to survive from one year to the next was 0.46 in males but only 0.37 in females, suggesting that higher female mortality may indeed be the most important predictor of male-biased adult sex ratios.
Keywords: dispersal; capture probability; site fidelity; true survival; Constant Effort Site (CES)